Clinical and molecular distinctions in patients with refractory colon cancer who benefit from regorafenib treatment - Lee, Min-Sang (Ther Adv Med Oncol, 2020)
Regorafenib (Stivarga, BAY 73-4506; Bayer Pharma AG, Berlin, Germany) is a novel oral multikinase inhibitor that blocks the activity of several protein kinases. However, few guidelines exist for novel biomarkers to select patients who will likely benefit from regorafenib treatment. Metastatic colorectal cancer (mCRC) patients treated with regorafenib were evaluated in this study. Tumor tissues of these patients were subjected to next-generation sequencing-based cancer panel tests. The relationship between molecular profiling and efficacy of regorafenib was analyzed. Among the 76 mCRC patients, the median age was 58 years (range 22–79 years), and 73.7% received regorafenib as a third-line therapy. The primary tumor locations were the right side (n = 15, 19.8%) and the left side (n = 61, 80.2%). Most patients (97.4%) had received prior anti-angiogenetic agents, and a prior anti-Epidermal Growth Factor Receptor (EGFR) agent had been administered to 32.9%. Of these 76 patients, 65 were evaluated to determine the efficacy of treatment. We observed zero complete responses, seven confirmed partial responses (PR 9.2%), 26 stable disease states (34.2%), and 32 disease progressions (42.1%). The overall confirmed response rate and the disease control rate were 9.2% and 43.4%, respectively. Genomic analysis revealed that APC mutations were significant in patients who demonstrated a tumor response to regorafenib (p < 0.05). Interestingly, FGFR1 amplification was detected in only three of 76 patients (3.9%), and these three patients achieved a PR to regorafenib. The median progression-free survival time was 2.8 months (95% Confidence Interval [CI] 1.6–4.0). Patients with BRAF mutation and/or SMAD4 mutation had significantly worse progression-free survival (PFS) than those without such a mutation. On pathway analysis, Tumor Growth Factor (TGF)-beta pathways were significantly associated with worse PFS. We found that efficacy of regorafenib might be correlated with specific genetic aberrations, such as APC mutation and FGFR1 amplification. In addition, SMAD4 mutation and TGF-beta pathway were associated with worse PFS after regorafenib. We found that efficacy of regorafenib might be correlated with specific genetic aberrations, such as APC mutation and FGFR1 amplification. In addition, SMAD4 mutation and the TGF-beta pathway were associated with worse PFS after regorafenib.